Results from the First Para Report Card on Physical Activity for Children and Adolescents with Disabilities in Chile - Cortinez-O'Ryan, A (Human Kinetics Publishers Inc., 2025)
Background: Global initiatives have been put in place to attain a thorough understanding of worldwide variations in physical activity (PA) among children and adolescents. Yet, there is limited knowledge about PA-related indicators, specifically for children and adolescents with disabilities (CAWD). To bridge this data gap, the Global Matrix of Para Report Cards (PRCs) of CAWD initiative was established to address the scarcity of information on PA for this population globally. The purpose of this manuscript is to summarize the results of Chile s First PRC on PA for CAWD. Methods: Chile s PRC included 10 core PA indicators common to the Global Matrix of PRCs. Evidence from scientific articles, reports, and databases available or released from 2018 to January 2022 was included for each indicator. A scientific committee collected and analyzed the data, assigning letter grades (A-F) based on benchmarks. Results: The grades assigned were as follows: Overall PA, D-; Organized Sports and Physical Activity Participation, C-; Active Play, INCOMPLETE; Active Transportation, D-; Sedentary Behavior, F; Physical Fitness, INCOMPLETE; Family and Peers, D+; School, C+; Community and Environment, D+; Government, B-. Conclusions: Chile scored low in most indicators. Although some efforts have been made in the last decade in terms of policies, these have not been reflected in PA and related behaviors in CAWD. The results underscore that maintaining the current situation is inadequate for addressing the widespread problem of physical inactivity among CAWD in Chile, emphasizing the urgency for substantial changes and a comprehensive approach to effectively combat this crisis. © 2025 Human Kinetics, Inc.